Ответы и объяснения

2012-12-04T16:13:53+04:00

1) 2х^2=3x

    2x^2-3x=0

    x(2x-3)=0

    x=0   или   2х-7=0

                     2х=7

                     х=3,5

 

2)2=7x^2+2

   2-7x^2-2=0

   -7x^2=0

   x=0

 

3)2x^2-8x+x-4=x^2-4

   2x^2-7x-4-x^2+4=0

   x^2-7x=0

   x(x-7)=0

   x=0   или   x-7=0

                   x=7

2012-12-04T16:15:06+04:00

2х^2-3х=0

а=2 b=3 c=0

по дискриминанту b^2+4ac 

получается 4) корень из 4 равен 2

x1=-b+корень из дискримананта \на 2*а

x1=-3+2делённое на 4

х1=-0,25

х2= -b-корень из дискримананта \на 2*а 

х2=-3,5

первое вроде так